A potential VEGF-driven hypothesis of calvarial centripetal proliferation in cerebral proliferative angiopathy - Shigeta Miyake; Timo Krings; Tze Phei Kee; Thierry A. G. M. Huisman (Scientific Reports)
Abstract Cerebral proliferative angiopathy (CPA) is a rare subtype of cerebral arteriovenous malformation, characterized by unique angiographic features and clinical presentations. Although the clinical and angiographic characteristics of CPA have been well described, their impact on the surrounding tissues remains underexplored. Herein, we investigated the presence of calvarial thickening in patients with CPA, and discuss its potential pathogenesis. This retrospective multicenter cohort study enrolled 16 CPA patients from our institutions. Patients were identified by a search of the hospital medical records for key words related to “cerebral proliferative angiopathy.” Data on demographics, CPA characteristics, clinical symptoms, and calvarial thickening were collected and analyzed using CT and MRI. Statistical analyses were performed using t-tests and Fisher’s exact tests, with significance set at P < 0.05. Patients with CPA ranged from 4 to 69 years of age and underwent skull evaluation at a median age of 26.5 years. Calvarial thickening was present in 43.8% of cases, predominantly affecting the frontal bone, and extending bilaterally. A trend toward calvarial thickening was observed in patients with concomitant signs of cerebral venous congestion (p = 0.06), while no significant association with age, sex, or symptoms was found. Calvarial thickening displayed centripetal proliferation with trabecular formation extending from the inner table. This study identified Calvarial centripetal proliferation in a significant proportion of patients with CPA. We hypothesized that this may be related to elevated vascular endothelial growth factor levels due to the proangiogenic nature of CPA.